Impact of Processing Method on Compressive Strength of Dried Yam Chips for Yam Flour Production - Dada, E.O.; Adewumi, H. O.; Adebayo, T. B.; Idowu, D. O. (Direct Research Journal of Agriculture and Food Science, 2024)
In the yam flour production, energy required for milling operation is of great importance to a flour miller. This work therefore, determines the effect of some selected processing parameter, on the compressive strength of yam chips prepare for making yam flour. To study the effect of these selected production variables on the compressive strength of dried yam pellet, a 5-level factorial response surface methodology (RSM) of design expert version 6.0.8 of 2002 was used to identify the relationship between the response function (compressive strength) and the selected process variable of the dried yam chips. The factors considered are soaking time 5, 10, 25, 40 and 55 minutes, soaking temperature (40, 60 ,80, 100 and 120, drying temperature 45, 60, 75, 90 and 105 °C and chips sizes in volume 20, 50, 90, 160 & 230 in the determination of compressive strength of the yam chips. The experiments were replicated six times. The RMS was used to get the functional relationships between the processing factors and the empirical model. The results were then validated using the coefficient of determinant (R2) from the design expert software. The compressive strength was observed to increase from 98.15 to 104.15 kN when the soaking time increased from 5 to 55 minutes. It was also observed that as volume increases from 20 to 160 cm3 the compressive stress also increases from 28.14 to 128.82 kN. Varieties was found to be insignificant on the mechanical compressive force of dried yam chips. The study concluded that in the selection of equipment and power equipment for milling dried yam for yam flour production the selected processing parameter should be taking into consideration for selection of accurate energy needed during milling of yam flour.